PENGEMBANGAN SISTEM INFORMASI MANAJEMEN LAYANAN PENUMPANG DI PELABUHAN NUSANTARA KENDARI (INTEGRASI DENGAN OPTICAL CHARACTER RECOGNITION) - Fidmasari, Rezki; Musaruddin, Mustarum; Mokui, Hasmina Tari (JUTIM (Jurnal Teknik Informatika Musirawas), 2024)
This study was conducted to analyze the implementation of the Passenger Service Management Information System at the Port of Nusantara Kendari by integrating it with Optical Character Recognition technology. This study uses a type of research with a qualitative approach where this research has been conducted at the Port of Nusantara Kendari from August-October 2024. The development of the Passenger Service Management Information System at the Port of Nusantara Kendari and integrated with technology such as Optical Character Recognition (OCR) encourages the efficiency of the administrative process, especially passenger services, especially in monitoring and managing passenger data in real time so that it can provide better information data to stakeholders and encourage increased user satisfaction at the Port of Nusantara Kendari.